Exploration of the environmentally benign and highly effective approach for improving carbon nanotube homogeneity in aqueous system - Zubir, M.N.M.; Badarudin, A.; Kazi, S.N.; Misran, M.; Ibrahim, R.; Amiri, A.; Sadri, R. (Kluwer (now part of Springer), 2016)
The present research highlighted the use of different plant-based phytochemical extracts on the dissolution of carbon nanotubes (CNTs) bundles in aqueous solution. Three new plant extracts (i.e., Cinnamon, Barley grass and Androganis Pinnaculata) were introduced in this research on top of the previously studied green tea and tannic acid as dispersants. FT-IR results strongly suggest the evidence of phenolic-rich component containing within each plant. Further, significantly low quantity of plant extract was required to isolate CNTs based on spectroscopy data. The results also suggest the existence of an optimum CNTs/plant extract proportion to promote higher rate of CNTs dissolution. The high level of CNTs affinity toward water was vindicated via contact angle measurement, indicating the successful encapsulation of phenolic compound on CNTs sidewall. Thermal conductivity measurement data showed as high as 18 % enhancement at very low CNTs concentration relative to base fluid which was attributed to the well-dispersed CNTs complexes. The rheological measurements exhibit Newtonian behavior identical to water and produce negligible increase in viscosity (i.e., less than 3 %), by which when combine with the much higher increase in thermal conductivity, paves a favorable condition toward achieving highly efficient thermal transport medium.